Material Flow Cost Accounting - Typical Case Study of a Japanese Pharmaceutical Company and Applicable Conditions for Vietnam - Nguyen, Thi Huong Lien (ĐHKT, 2016)
Study features of MFCA, an effective tool of environmental management accounting, potential benefits of MFCA over traditional material cost accounting method.